Torque hysteresis controller for brushless dc motor drives - Noor Azam, Ahmad Faiz; Manap, Mustafa; Jidin, Auzani; Bahari, Norhazilina; Jopri, Mohd Hatta; Abdullah, Abdul Rahim (2012)
The presence of the commutator and brushes in a dc machine enforce severe limitations on its voltage and current ratings, means that the output power capability of a dc machine is restricted. The mechanical commutator in a dc machine limits its high speed capabilities. Both the brushes and commutator of a dc machine require regular maintenance. In addition, dc machines are prone to sparking and cannot be normally used in explosive atmosphere. The dust produced by brush wear, makes the dc machine undesirable for use in certain industries like the semiconductor or food industries. Thus, to overcome this problem BLDC machine is proposed due to its advantages over the conventional dc machine. The torque hysteresis controller is presented as the technique chosen to control the phase current and torque of the BLDC machine. This method used to replace the voltage control in BLDC machine. Voltage control is conventional methods used but have a very high current overshoot, by using torque hysteresis controller it will provide current protection which is the value of current and torque will stay within certain limits around with reference value